The City in Songs, Songs in the City: The Image of New York in the Folk Music of the 1960s - Racek, Tomáš (Univerzita Pardubice, 2017)
This bachelor thesis is concerned with the image of New York City in the folk music of the 1960s, specifically in the song lyrics of the North American singer-songwriters Bob Dylan, Paul Simon, Joni Mitchell, Fred Neil, Phil Ochs, John Phillips, John Sebastian and Joey Levine. The theoretical part provides historical and cultural background of the city and its folk music in the chosen time period. The analytical part then explores the main themes and tendencies in the depiction of the metropolis in the chosen lyrics. The results of the thesis are summarized in the conclusion.
Město v Písních, Písně ve Městě: Zobrazení New Yorku ve Folkové Hudbě 60. let
Keywords: New York; folk music; 1960s; city; lyrics; New York; folková hudba; 60. léta; město; písňové texty